PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS PIDATO - Pitsantia Pitsantia; Yenny Puspita; Darwin Effendi (Universitas Negeri Makassar, 2025)
This study aims to describe the effect of Think Pair Share learning model on speech text writing skills in class VIII students of SMP Negeri 1 Air Kumbang. The research used true experimental design model only postest control group. The data collection techniques in this study used observation data and test data. Data analysis techniques used in this research are descriptive and inferential statistics. The results showed that the value of tcount 4.831> from ttable 1.677 which means that Ho is rejected and Ha is accepted. This proves that the Think Pair Share learning model has an effect on the speech text writing skills of class VIII students of SMP Negeri 1 Air Kumbang.